Pentahelix Education: Collaborative Synergy to Reduce Stunting Prevalence - Khotimah, Khusnul; Sintiawati, Nani; Hilmi, Muhammad Irfan; Kusumawardani, Erma (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2025)
Stunting is a growth failure condition experienced by children under two. Efforts to reduce stunting are carried out through two nutritional interventions: specific and sensitive. The Pentahelix approach is worth studying to foster collaboration and alliance in stunting prevention education. This research aims to develop a Pentahelix educational formulation to strengthen specific and sensitive intervention services for the stunting reduction program in the Jember Regency. The research method used is a mixed methods research type. The mixed methods approach or mixed method approach is a research approach that involves the integration or unification of qualitative and quantitative data research. This research is located in the Jember Regency, with respondents including parents, the community, stunting program managers, and stakeholders. The Pentahelix formulation development research results began with planning the learning program. The first step is to conduct a specific and sensitive service assessment. The assessment results are used to develop an education service menu based on the local context and community needs. The final component is the alliance among the Pentahelix elements. Evidence-based policy collaboration is produced through the cooperation of the government and academics, while the media and community deliver direct education using materials prepared by academics. Business actors help ensure sustainable access by providing infrastructure or supporting products. Academics and the government monitor and evaluate the program's effectiveness for future policy improvements. The results of the Pentahelix-based learning program begin with a community assessment, which is an evaluation process to understand the community's needs and the program's effectiveness.